Post-traumatic growth among the UK veterans following treatment for post-traumatic stress disorder. Issue 2 (22nd July 2016) - Murphy, Dominic; Palmer, E; Lock, R; Busuttil, W
Abstract : Introduction: The aim of this paper was to examine levels of post-traumatic growth (PTG) in a sample of the UK veterans who had received treatment for post-traumatic stress disorder (PTSD). Methods: The study followed-up 149 UK veterans after they had completed standardised treatment for PTSD provided by Combat Stress. Data had previously been collected on a range of mental health outcomes before treatment, and then repeated 6 months after the end of treatment. For the current study, participants completed the post-traumatic growth inventory (PTGI) measure. Analysis was conducted to explore levels of PTG and whether there were any relationships between pretreatment and post-treatment ratings of mental health and PTG. Results: The mean score on the PTGI was 32.6. Evidence of a treatment effect on levels of PTG was observed. There appeared to be a relationship between improvements in symptoms of PTSD and depression and higher levels of PTG. Conclusions: This study observed the presence of PTG following exposure to traumatic events within a sample of the UK veterans following their treatment for PTSD. PTG scores were moderately low in comparison to similar studies in the USA.